(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the development of a selection program for track and field events based on the anthropometric indicators and physical qualities of athletes at the initial training stage. According to the survey analysis, it is necessary to introduce numerous changes in organizing the training sessions, including continuous planning of lessons and the use of various methods and techniques. When designing training programs, it is important to consider the athletes’ functional preparedness, use technical preparedness indicators for classification in track and field events, and focus on using simple physical education tools and pedagogical methods more frequently.